The invisible safety net : protecting the nation's poor children and families - Currie, Janet M. (Princeton University Press, 2006)
The modern social safety net is under attack. So argues economist Janet Currie in one of the most provocative books ever published on America's social welfare system. Unlike most books about antipoverty programs, Currie trains her focus on cash welfare, which accounts for a small and shrinking share of federal expenditures on poor families with children, but on the staples of today's American welfare system: Medicaid, Food Stamps, Head Start, WIC, and public housing. These programs, Currie maintains, form an effective, if largely invisible and haphazard safety net, and yet they are the very programs most vulnerable to political attack and misunderstanding. This book highlights both the importance and the fragility of this safety net, arguing that, while not perfect, it is essential to fighting poverty. Currie demonstrates how America's safety net is threatened by growing budget deficits and by an erroneous public belief that antipoverty programs for children do not work and are riddled with fraud. By unearthing new empirical data, Currie makes the case that social programs for families with children are actually remarkably effective. She takes her argument one step further by offering specific reforms, detailed in each chapter, for improving these programs even more.